Job Mobility and Assortative Matching - Luisa Braunschweig; Wolfgang Dauth; Duncan H.W. Roth (Institute of Labor Economics (IZA), 2024)
We examine the development of worker-firm matching over the career due to job mobility. Using administrative employer-employee data covering the universe of German employees, we measure the degree of assortative matching as the correlation of worker and firm quality measures obtained from an AKM wage decomposition. We also introduce a novel measure based on the distance between the estimates of worker and firm quality. Both measures indicate that the degree of assortative matching, on average, increases with each job move. For high-quality workers, this can be explained by job ladder models as these workers move to higher-quality firms. Low-quality workers are matched less assortatively at the beginning of their careers, but also manage to climb the job ladder at first. For this group, the increase in assortative matching increases after the third job, when they fall down the job ladder. Changes in worker-firm matching are also relevant for the extent of life cycle inequality. We estimate that the increase in assortative matching accounts for around 25% of the increase in wage inequality over the life cycle.
Keywords: J23; J24; J31; J62; 330; assortative matching; wage decomposition; job mobility; life cycle; wage inequality; firms